Manipulating the ordered oxygen complexes to achieve high strength and ductility in medium-entropy alloys - Jiao, Meiyuan; Lei, Zhifeng; Wu, Yuan; Du, Jinlong; Zhou, Xiao-Ye; Li, Wenyue; Yuan, Xiaoyuan; Liu, Xiaochun; Zhu, Xiangyu; Wang, Shudao; Zhu, Huihui; Cao, Peipei; et al. (Nature communications, 2023)
Oxygen solute strengthening is an effective strategy to harden alloys, yet, it often deteriorates the ductility. Ordered oxygen complexes (OOCs), a state between random interstitials and oxides, can simultaneously enhance strength and ductility in high-entropy alloys. However, whether this particular strengthening mechanism holds in other alloys and how these OOCs are tailored remain unclear. Herein, we demonstrate that OOCs can be obtained in bcc (body-centered-cubic) Ti-Zr-Nb medium-entropy alloys via adjusting the content of Nb and oxygen. Decreasing the phase stability enhances the degree of (Ti, Zr)-rich chemical short-range orderings, and then favors formation of OOCs after doping oxygen. Moreover, the number density of OOCs increases with oxygen contents in a given alloy, but adding excessive oxygen (>3.0 at.%) causes grain boundary segregation. Consequently, the tensile yield strength is enhanced by ~75% and ductility is substantially improved by ~164% with addition of 3.0 at.% O in the Ti-30Zr-14Nb MEA. Ordered oxygen complexes (OOCs) endow a unique interstitial strengthening mechanism for simultaneously enhancing strength and ductility in HEAs. Here, the authors demonstrate whether such mechanism can be extended to other alloy systems and how the formation of OOCs is tailored.